2014
DOI: 10.1016/j.physio.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Relevant patient perceptions and experiences for evaluating quality of interaction with physiotherapists during outpatient rehabilitation: a qualitative study

Abstract: This study identified which elements of the physiotherapist-patient interaction are considered by patients when evaluating the quality of care in rehabilitation outpatient settings. Further research should work to develop self-report questionnaires about patients' experiences of the physiotherapist-patient interaction in rehabilitation services to provide empirical and quantitative evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 26 publications
0
48
0
2
Order By: Relevance
“…Then, 58 studies were excluded as reported in Supplementary Table S2. Finally, after having achieved the agreement among authors, articles [39,40,41,42,43,44,45,46,47,48,49] describing findings of 9 original studies were included: 2 studies produced 2 unique articles [42,43,45,46] presenting findings on the same samples for different study aims. The inclusion process is shown in figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, 58 studies were excluded as reported in Supplementary Table S2. Finally, after having achieved the agreement among authors, articles [39,40,41,42,43,44,45,46,47,48,49] describing findings of 9 original studies were included: 2 studies produced 2 unique articles [42,43,45,46] presenting findings on the same samples for different study aims. The inclusion process is shown in figure 1.…”
Section: Study Selectionmentioning
confidence: 99%
“…A total of 362 participants (193 females; 169 males) were included in the studies ranging from 10 [49] to 57 [41,45,46] per study, with a range of age between 18 [40] and 82 [42,43,49] years. Studies were performed in Spain [41,45,46], Australia [47,48,49], and England [42,43,44] by including patients cared for different musculoskeletal complaints [41,42,43,45,46,47,49].…”
Section: Characteristic Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiotherapy is adopting a biopsychosocial model [17], acknowledging that individual experiences, such as the social, cultural, psychological and contextual factors of a person exercise a strong influence on pathology and recovery [18]. Under this new paradigm, the establishment of PCC and a relationship between physiotherapists and those who receive care appear to be key for therapeutic success [19][20][21]. Indeed, there is a strong consensus among and analysis, decision to publish, or preparation of the manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…The CBR activity schedule, which was 4 days per week for centerbased and 1 day for home-based, was considered as an acceptable routine as it was very difficult to find childcare with trained workers. 12 The CBR activity was also highlighted to encourage the socialization of disabled children and prevent isolation among them.…”
Section: Discussionmentioning
confidence: 99%